Parents' Weekend a capella show in Goddard Chapel. Photo 052 - Loeb, Brian (Tufts Archival Research Center, 2008)
Parents' Weekend a capella show in Goddard Chapel. Performances by the Amalgamates, the Jackson Jills and the Beelzebubs.